The Portuguese referee performance model - Mendes, Sérgio (2022)
The concern with the performance of football referees has opened lines of investigation in areas such as technical and physical performance. Theoretical and analytical gaps regarding the causes of their performances in a holistic perspective are scarce. The purpose of this study is to understand how various processes of personal, career development and contextual nature influences the classification of football referees. The literature review on excellence and the performance of the referees allowed to define a model that contemplates three distinct areas: 1) personal experience; 2) sports course; 3) surrounding context. The model to understand the causes of the performance of the Portuguese referees was obtained by comparing the classification of referees for national boards between the periods of 2009-10 and 2018-19 with the relative data to their age, experience as a federated player and referee, region density and proximity to peers of national board. The results show that the performance of the referees is influenced by a set of processes such as individual experience, sporting background and the context. This article opens a new perspective on the referees' training process. Its content may constitute an important insight for the implementation of referee training programs, namely at the base.